Do you like me? Behavioral and physical features for socially and emotionally engaging interactive systems - Esposito, Anna; Amorese, Terry; Cuciniello, Marialucia; Esposito, Antonietta M.; Cordasco, Gennaro (Frontiers in Computer Science, 2023)
With the aim to give an overview on the most recent discoveries in the field of socially engaging interactive systems, the present paper discusses features affecting users’ acceptance of virtual agents, robots, and chatbots. In addition, questionnaires exploited in several investigations to assess virtual agents, robots and chatbots (only voice) acceptance are discussed and reported in the appendix as additional material, to make them available to the scientific community. These questionnaires were developed by the authors as scientific contribute to the H2020 project EMPATHIC (http://www.empathic-project.eu/www.empahtic), and Menhir (https://menhir-project.eu/) and the Italian funded project SIROBOTICS (https://www.exprivia.it/it-tile-6009-si-robotics/) and ANDROIDS (https://www.psicologia.unicampania.it/android-project) to guide the design and implementation of the promised assistive interactive dialog systems. They aimed to evaluate quantitatively Virtual Agents Acceptance (VAAQ), Robot Acceptance (RAQ) and Synthetic Virtual Agent Voice Acceptance (VAVAQ).